The Political Organization of Rus' in the 10th Century - Petr S Stefanovich (Jahrbücher für Geschichte Osteuropas, 2016)
This study is an attempt to present the political organization of Rus' in the 10th century reevaluating the much debated role of the Scandinavians in the formation of the Rus'ian polity. A large number of Scandinavians (mostly from Sweden and Gotland) migrated to Eastern Europe in the 9th - middle of the 11th centuries. This fact is clear from the historical, linguistic and archeological evidence accumulated to date. However, much is unclear about the results and significance of this migration. Particularly controversial is the question if and how it came to be related with the formation of the political structures of Rus' which united a variety of peoples (gentes) in Eastern Europe in the 10th - 11th centuries. In this paper I examine the elite of Kievan Rus' in the middle of the 10th century. The original sources from that time give us some valuable information on the political organization and social hierarchy of Rus'. Two of these sources are of particular importance: the treaty of 944 between Rus' and Byzantium (a copy is included in the Tale of Bygone Years) and the description of the embassy of Olga, princess of Rus', to Constantinople in 957 given by the Byzantine Emperor Constantine Porphyrogenitus in his treatise De Ceremoniis (II, 15). In my opinion there is some corresponding evidence on Rus' in these two texts which has not been noticed or articulated in the debates on the texts. Emphasizing these correspondences and referring to the witnesses of other sources I attempt a consistent description of the elite of Kievan Rus'. I conclude that the Rus' of the middle of the 10th century was, politically and territorially, an association of 25 non-tribal administrative units located mostly along the famous "Route from the Varangians to the Greeks". These units or most of them were headed by Scandinavian leaders who formally recognized a superiority of the Kievan prince. This model disagrees sharply with the picture created by the Rus'ian chronicles of the 11th - early 12th centuries which exalt the Rurikid dynasty and do not mention in their narratives any other competing leaders or clans. My study aims at verifying this picture and considering a contribution of the Scandinavians to political developments in medieval Rus'.